A critical analysis of Caribbean creative industries : the way forward - Whyte-Givans, Sophia (CCS GeorgetownGY, 2006)
Looks at the lack of coordination and its implications for Jamaica, at Jamaica's cultural policy and also at an example of the creative industries from the perspective of a publisher with a regional presence. Explores CARICOM's role in mapping the future of the creative industries. Applies the experiences of WIPO to a macro-economic framework that is currently used in Jamaica. Provides a blueprint for the future of the creative industries.